Soil and water conservation measures to adapt cropping systems to climate change facilitated water stresses in Africa - Brempong, Mavis Badu; Amankwaa-Yeboah, Patricia; Yeboah, Stephen; Owusu Danquah, Eric; Agyeman, Kennedy; Keteku, Agbesi Kwadzo; Addo-Danso, Abigail; Adomako, Joseph (Frontiers in Sustainable Food Systems, 2023)
Complex controls and non-linear responses of the climate system to global warming make it difficult to have clear-cut predictions of future precipitation amounts and timelines. It is, however, evident from current observations that some predictions of unusually high rates of flooding and droughts are occurring and threatening food security in sub-Saharan Africa (SSA). The impact of climate change is immense on SSA though it contributes the least to climate change globally. Crops face lots of growth challenges which reduce their productivity under drought and flood conditions. SSA must prepare agricultural soils for the anticipated climate variabilities, to ensure sustainable food availability. The effort to adapt soils to climate change must be a concerted one, using technologies from various facets of science. Stakeholders must adopt water-smart strategies that maintain proper soil-water balance. They should focus on manageable inherent soil properties that control the susceptibility/adaptability of cropping systems to climate change. Conservation agriculture techniques that target improving soil organic matter and maintaining soil life; protecting the soil from compaction and erosion; reducing soil disturbance; enhancing soil infiltration and groundwater recharge capacity, must be applied to our soils. A number of these techniques equip the soils to be better sinks of excess water in flood-prone areas and improve water-holding capacities in drought-prone ones. Governments, farmers, and all stakeholders must also invest in both simple and complex water harvesting/ re-directing infrastructure which conserve water for future use. Water-efficient irrigation systems must be employed by farmers during water scarcity. Most importantly, gaps between research, industry, farmers, and governments must be bridged to for easy flow of information on improved technologies and quick adoption of climate change mitigation strategies.